Bodies, minds, and design – An integrated approach to museum innovation - Antonella Rosmino (Agathón)
This paper explores the impact of emerging technologies, with a particular focus on Brain-Computer Interfaces (BCI), within the museum experience. Analysing various case studies highlights the potential of BCIs in visual communication design to personalise the interaction between the visitor and artwork, making experiences more engaging and meaningful. To overcome the limitations of current approaches, the paper proposes a reflection on an integrated model that combines neuroscience, design, and the humanities, centred on the individual and their interaction with the environment. This interdisciplinary approach, which lacks established design traditions in Visual Communication for Cultural Heritage, aims to offer new research perspectives to enhance individual perceptions during multisensory experiences of cultural heritage.